2002
DOI: 10.1257/00028280260136255
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Policy, Profits, and Investment

Abstract: This paper evaluates the effects of fiscal policy on investment using a panel of OECD countries. We find a sizeable negative effect of public spending—and in particular of its wage component—on profits and on business investment. This result is consistent with different theoretical models in which government employment creates wage pressure for the private sector. Various types of taxes also have negative effects on profits, but, interestingly, the effects of government spending on investment are larger than t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
378
4
22

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(445 citation statements)
references
References 33 publications
41
378
4
22
Order By: Relevance
“…The consumption function (1) gives consumption according to the standard intertemporal consumption model, where there is a desire to smooth consumption, which therefore is determined by the present value of disposable income.…”
Section: Ricardian Equivalencementioning
confidence: 99%
See 2 more Smart Citations
“…The consumption function (1) gives consumption according to the standard intertemporal consumption model, where there is a desire to smooth consumption, which therefore is determined by the present value of disposable income.…”
Section: Ricardian Equivalencementioning
confidence: 99%
“…This link to expectations may cause non-linearities or state dependencies in the effects of fiscal policy, that is, the effects of fiscal policy intervention may depend critically on the initial policy situation. To see how this can arise, consider first a case where Ricardian Equivalence holds implying that the expected present value of public consumption is influencing private consumption, cf.. (1). Assume that public consumption follows a stochastic process with upward drift, and that it fluctuates within an upper and lower bound (Bertola and Drazen (1993)).…”
Section: Expectationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their empirical findings attested to a clear negative association between unit labour costs and profit margins. Alesina et al (2002) examined the effects of various fiscal variables on profits, proxied by gross profits per unit of capital in the business sector. They found that all revenues and spending variables exert a negative impact on profits with government wages having the largest negative effect (mostly through their influence on private sector wage outcomes).…”
Section: Empirical Setupmentioning
confidence: 99%
“…The evidence is more mixed, though, in emerging market economies where procyclical spending bias, narrow automatic stabilizers and limited credit access have constrained governments' ability to provide fiscal stimulus during adverse economic periods (Kaminsky, Reinhart and Vegh 2004). Initial fiscal conditions generally play a key role in crisis responses, in both advanced and emerging economies (Alesina et al 2002).…”
Section: The Sustainable Growth Of Public Debtmentioning
confidence: 99%